Pengembangan Alat Ukur Psikometri Maladaptive Coping Scale (MCS) - Maharani, Intan Tirana; Islam, Azizah Fajar (Universitas Airlangga, 2025)
Maladaptive coping refers to ineffective stress management strategies that have the potential to worsen an individual's psychological condition. These strategies include internalizing behaviors such as withdrawal and self-blame, as well as externalizing behaviors such as impulsivity and aggression. This study aimed to develop the Maladaptive Coping Scale (MCS), based on the framework of Early Maladaptive Schemas (EMS). A quantitative approach was employed for instrument development, involving 250 participants aged 18 – 30 years. It consisted of 36 items covering two dimensions and four subdimensions. Content validity tested using CVI showed that 27 items were valid (I-CVI ≥ 0.78). Reliability tested using Cronbach’s Alpha yielded (a = 0.875). A chi-square test showed a balanced distribution of responses (p = 1.000). This conclude that the MCS is a valid and reliable instrument for identifying maladaptive coping strategies and can be used in psychological assessment and culturally contextualized interventions in Indonesia. Keywords: maladaptive coping, early maladaptive schemas, internalizing, externalizing, instrument development